Implementasi Program Bangga Kencana Dalam Mewujudkan Fungsi Keluarga Sebagai Pencegahan Kekerasan Seksual Anak Nagan Raya - Sartika, Lilis; Safrida, Safrida (Sawala : Jurnal Administrasi Negara, 2023)
The rise of cases of sexual violence against children, the government of Nagan Raya Regency is here to help minimize the disaster through the realization of the Bangga Kencana program. The purpose of this research is to find out the implementation steps of the program in the field by referring to the Van Horn & Van Meter theory. The method used is a qualitative research method by collecting data through observation, documentation and the results of interviews with the government and the people of Nagan Raya Regency. The results of this study concluded that the implementation of Bangga Kencana through the formation of BKR, PIKR and GenRe groups was carried out by following the guidelines and directions from BKKBN although there were still some obstacles during the implementation of activities with cadre groups who were being fostered to become role models for other communities regarding the importance of awareness of understanding family functioning and sensitivity to protection against sexual violence experienced by children